AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOL KULIT BUAH RAMBUTAN (Nephelium lappaceum L. ) TERHADAP PENANGKAPAN RADIKAL BEBAS DPPH - Hady Anshory; Suparmi Suparmi; Arif Setiadi Tamimy (Jurnal Ilmiah Farmasi, 2006)
ABSTRACTRambutan fruits are consumed by people for additional food and medical use. Pericarp oframbutan has been known to have some active compounds such as flavonoid. Many flavonoidsfrom plants are known to have anti radical activity effect or antioxidant. It is very interest todetermine of antioxidant activity from ethanol extract of rambutan pericarp (Nephelium lappaceumL.). Antioxidant activity was carried out spectrophotometry by using DPPH (2,2-diphenyl-1-picrylhydrazyl) as a reagent. The extract and vitamin E (-tocoferol) concentration was made 2, 3,4, 5, and 6 g/ml. The increasing concentration of extract and vitamin E has caused the scavengingof free radical DPPH. The amount of free radical scavenging DPPH was calculated based on itsabsorbance, measured at  521 nm. The result showed that anti radical activity of ethanolic extractof rambutan pericarp (EC50 = 1,62 g/ml) is higher than that of vitamin E (EC50 = 2,91 g/ml).Keywords : Rambutan, antioxidant, free radical DPPH